Growth dynamics of splenic artery aneurysms: morphology, comorbidities, and vascular anatomical factors - Ahmet Tanyeri; Aygün Katmerlikaya; Rıdvan Akbulut; Mehmet Burak Çildağ (BMC Medical Imaging)
Abstract Background Splenic artery aneurysms (SAAs) are the most common visceral artery aneurysms, often detected incidentally due to the widespread use of cross-sectional imaging. While many remain asymptomatic, rupture carries a high mortality risk. Despite established size-based treatment guidelines, the impact of morphological features, vascular anatomical factors, and comorbidities on SAA growth remains unclear. This study investigates the long-term growth dynamics of SAAs and their associated risk factors. Methods This retrospective cohort study included 49 patients with true SAAs who were assessed between 2014 and 2024. The annual change in aneurysm size was calculated by measuring the difference in diameter between the initial and final computed tomography scans. Aneurysm growth was analysed in relation to morphological characteristics (mural thrombus, wall calcification), vascular anatomical factors (coeliac artery stenosis, splenic artery, superior mesenteric artery, and aortic diameters), and comorbidities (smoking, hypertension, atherosclerosis, etc.). Data were analysed using the Mann-Whitney U test, Kruskal-Wallis test, and chi-square test. A multivariable regression analysis was performed to assess the impact of comorbidities on aneurysm growth, while receiver operating characteristic (ROC) analysis was conducted to determine the predictive threshold value. A p < 0.05 was considered statistically significant. Results The mean age of the study cohort was 71 ± 16 years, with 43% of the patients being male. Aneurysm growth was observed in 45% of patients, while stability and regression were noted in 18% and 37%, respectively. The median initial maximum aneurysm diameter was 16.4 mm (8.4–36). The median growth rate was 0.55 mm/year, whereas the median regression rate was 0.86 mm/year. Aneurysm growth was significantly associated with smoking (p = 0.0001), mural thrombus presence (p = 0.021), absence of wall calcification (p = 0.041), younger age (p = 0.013), and a larger abdominal aortic diameter (p = 0.023). ROC analysis identified an initial aneurysm diameter of ≥ 17 mm as a predictive threshold for growth. Conclusion The growth dynamics of splenic artery aneurysms are heterogeneous, with smoking, mural thrombus presence, younger age, and a larger abdominal aortic diameter identified as key factors associated with aneurysm growth. Guidelines should be refined and strengthened with patient-specific follow-up and treatment algorithms based on updated clinical data. Clinical trial number Not applicable.